Humility in organizations: a bibliometric study - Renato Cuenca; Patricia Amelia Tomei; Sylvia Freitas Mello (Cadernos EBAPE.BR, 2022)
Abstract Humility is a characteristic little studied in the organizational environment. The interest in research on humility started to gain some representativeness this century. However, literature reviews on humility in management are rare, making it necessary to systematize the relevant knowledge in this field. This research highlights the intellectual structure of the domain, the current studies, and research opportunities associated with humility in organizations. A bibliometric study was carried out from 2000 to 2020, and activity and relationship indicators, such as co-citations and bibliographic coupling, were analyzed. Results show three major thematic lines that make up the intellectual structure of the field: (i) concepts, antecedents, and organizational attributes, (i) methods and scales, and (iii) behavioral issues. This research is organized on four major fronts: (i) expressed humility, (ii) humility and CEOs, (iii) humility and teams, and (iv) humility and organizational behavior. Finally, an agenda for future research is presented, emphasizing the analysis of how expressed humility and humble behavior can be taught and internalized in the organizational culture.